National archival platform system design using the microservice-based service computing system engineering framework - Taufik Iqbal Ramdhani; Ninon Nurul Faiza (Computer Science and Information Technologies, 2023)
Archives play a vital function concerning the dynamics of people and nations as an instrument to treasure information in diverse domains of politics, society, economics, culture, science, and technology. The acceleration of digital transformation triggers the implementation of a smart government that supports better public services. The smart government encourages a national archival system to facilitate archive producers and users. The four electronic-based government system (SPBE) factors in the archival sector and open archival information system (OAIS) as a data preservation standard are the benchmarks in developing this study's national archival platform system. An improved service computing system engineering (SCSE) framework adapted to the microservice architecture is used to aid the design of the national archival platform system. The proposed design met the four-factor service design validation of coupling, cohesion, complexity, and reusability. Also, the prototype suggests what resources are needed to put the design into action by passing the performance test of availability measurement.